Complete genomic DNA sequence of the East Asian spotted fever disease agent Rickettsia japonica. - Minenosuke Matsutani (Public Library of Science (PLoS), 2013)
Rickettsia japonica is an obligate intracellular alphaproteobacteria that causes tick-borne Japanese spotted fever, which has spread throughout East Asia. We determined the complete genomic DNA sequence of R. japonica type strain YH (VR-1363), which consists of 1,283,087 base pairs (bp) and 971 protein-coding genes. Comparison of the genomic DNA sequence of R. japonica with other rickettsiae in the public databases showed that 2 regions (4,323 and 216 bp) were conserved in a very narrow range of Rickettsia species, and the shorter one was inserted in, and disrupted, a preexisting open reading frame (ORF). While it is unknown how the DNA sequences were acquired in R. japonica genomes, it may be a useful signature for the diagnosis of Rickettsia species. Instead of the species-specific inserted DNA sequences, rickettsial genomes contain Rickettsia-specific palindromic elements (RPEs), which are also capable of locating in preexisting ORFs. Precise alignments of protein and DNA sequences involving RPEs showed that when a gene contains an inserted DNA sequence, each rickettsial ortholog carried an inserted DNA sequence at the same locus. The sequence, ATGAC, was shown to be highly frequent and thus characteristic in certain RPEs (RPE-4, RPE-6, and RPE-7). This finding implies that RPE-4, RPE-6, and RPE-7 were derived from a common inserted DNA sequence.